Analisis Terhadap Efektivitas Perlindungan Konsumen dalam Transaksi Online Shop di Indonesia - Hasyim, Hasyim; Azhizah, Nurul; Devi, Sri Rahayu (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2025)
This research is motivated by the increasing number of online shop transactions in Indonesia, which are accompanied by various consumer protection issues, such as products that do not match the description, personal data leaks, and the lack of effective complaint mechanisms. The purpose of this study is to evaluate how effective the applicable consumer protection laws are and to find obstacles in their implementation. The study uses a qualitative descriptive approach, using literature studies and analysis of consumer reports from social media. The results of the study show that although regulations such as UUPK, UU ITE, and PP PSTE are available, their implementation is still not optimal due to low consumer literacy, weak supervision, and lack of coordination between institutions. The implications of these findings indicate the need to strengthen law enforcement, consumer education, and the application of technology for data protection and supervision of business actors. This study contributes to improving policies and increasing the security of digital transactions in Indonesia.